Countering agribusiness: Analyzing the potentials for agroecology in Mendoza’s Valle de Uco through a territorial perspective - Dorn, Felix M. (2025)
Agribusiness plays a key role in current climate and food crises, and agricultural change is a recurrent topic in transition studies. In Argentina, many question the industrialized food sector, proposing agroecology as an onto-epistemological alternative. This paper analyzes the potential for countering agribusiness in Mendoza's Valle de Uco through a territorial approach, understanding territoire as the material, ideological, and institutional relations among humans and with non-humans. Our analysis highlights agroecology's potential through collective values, value chain control, and healthy food demand, but also reveals limited institutional support, funding access, and minimal public contestation due to the strong regional wine identity.